1995
DOI: 10.1002/etc.5620140603
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenation of chlorinated dioxins by an anaerobic microbial consortium from sediment

Abstract: Anaerobic microorganisms enriched from Rhine River sediments are able to remove chlorine substituents from poly‐chlorinated dibenzo‐p‐dioxines (PCDDs). A model PCDD, 1,2,3,4‐tetrachlorodibenzo‐p‐dioxin (1,2,3,4–TeCDD) was reduc‐tively dechlorinated to both 1,2,3–and l,2,4–trichlorodibenzo‐/>‐dioxins (1,2,3–and 1,2,4–TrCDD). These compounds were further dechlorinated to 1,3–and 2,3–dichlorodibenzo‐p‐dioxins and traces of 2–monochlorodibenzo‐p‐dioxin. This is the first report in the literature of the anaerobic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 42 publications
3
53
1
Order By: Relevance
“…Thus, the complete dechlorination of PCDD/Fs seemingly took place in the microcosm. This observation contrasts with those in previous studies of dechlorinating microbial consortia, in which PCDD/Fs decreased with the significant accumulation of less-chlorinated DD and DF (1,9,11,12,15,65). The discrepancy between the previous results and ours might be due to differences in the conditions used for dechlorination.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, the complete dechlorination of PCDD/Fs seemingly took place in the microcosm. This observation contrasts with those in previous studies of dechlorinating microbial consortia, in which PCDD/Fs decreased with the significant accumulation of less-chlorinated DD and DF (1,9,11,12,15,65). The discrepancy between the previous results and ours might be due to differences in the conditions used for dechlorination.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies on the microbial reductive dehalogenation of PCDD/Fs as well as of PCBs started appearing in the 1990's, using anaerobic sediment microcosms and mixed cultures 2,3,13,14,19,20,26,47,72,127) , although no phylogenetic information about PCDD/F-dechlorinating enrichment cultures had been available until the discovery of the ability of "Dehalococcoides" to dechlorinate PCDD/Fs. In 2003, Bunge et al 25) reported that "Dehalococcoides" sp.…”
Section: Pcdd/f-dehalogenating Bacteria and Consortiamentioning
confidence: 99%
“…(3) Biodegradation effect. Some literatures (Adriaens and Grbic-Galic, 1994;Beurskens et al, 1995) had reported anaerobic biodegradation for some PCDD and PCDF congeners in sediments. The declining dioxins levels in this study were mainly due to the dilution effect of the flood.…”
Section: Declining Pcdd/f Levels In Sediments With Temporal Trendsmentioning
confidence: 99%